An Analysis of Digital Institutional Capacity and Personal Data Protection Policy Implementation in Indonesia : A Systematic Literature Review - Abednego Briantama; Muhamad Yopan (Journal of Law, Politic and Humanities, 2026)
This study conducts a systematic literature review to examine institutional capacity in the implementation of personal data protection policy, with particular reference to Indonesia’s Ministry of Communication and Digital Affairs (Komdigi). Despite the enactment of Law Number 27 of 2022 on Personal Data Protection, persistent data breaches and institutional fragmentation raise critical questions about the readiness of public institutions to enforce such policy. Utilizing the PRISMA 2020 protocol, this review identifies and synthesizes 27 peer-reviewed articles published between 2023 and 2025 from Scopus, Cambridge, and Taylor & Francis databases. The analysis reveals four principal themes: structural and regulatory capacity, human resource and technological capacity, inter-institutional coordination, and institutional values and ethics. Findings indicate that effective data protection governance depends not merely on the existence of legal frameworks but on the adaptive, coordinative, and ethical capacities of implementing institutions. The review further highlights significant gaps in longitudinal research and calls for deeper empirical investigation into how digital institutional capacity shapes policy outcomes in developing countries.